2009
DOI: 10.1051/0004-6361/200811326
|View full text |Cite
|
Sign up to set email alerts
|

MAGIC upper limits to the VHE gamma-ray flux of 3C 454.3 in high emission state

Abstract: Aims. We report upper limits to the very high energy flux (E > 100 GeV) of the flat spectrum radio quasar 3C 454.3 (z = 0.859) derived by the Cherenkov telescope MAGIC during the high states of July/August and November/December 2007. We compare the upper limits derived in both time slots with the available quasi-simultaneous MeV-GeV data from the AGILE γ-ray satellite and interpret the observational results in the context of leptonic emission models. Methods. The source was observed with the MAGIC telescope du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…On the other hand, the soft X-ray data were only a little bit lower than in November. Despite the softer synchrotron bump, γ -ray data showed in the SED the persistence of a hard peak at 1 GeV, similar to the higher states observed by AGILE in 2007 July and 2007 November (Anderhub et al 2009;Vercellone et al 2009). In fact, the December γ -ray spectrum (characterized by a photon index of ∼1.78) is consistent with those obtained during the two previous AGILE observations.…”
Section: Spectral Modelingsupporting
confidence: 68%
See 1 more Smart Citation
“…On the other hand, the soft X-ray data were only a little bit lower than in November. Despite the softer synchrotron bump, γ -ray data showed in the SED the persistence of a hard peak at 1 GeV, similar to the higher states observed by AGILE in 2007 July and 2007 November (Anderhub et al 2009;Vercellone et al 2009). In fact, the December γ -ray spectrum (characterized by a photon index of ∼1.78) is consistent with those obtained during the two previous AGILE observations.…”
Section: Spectral Modelingsupporting
confidence: 68%
“…The source was found to be in flaring state with an average γ -ray flux above 100 MeV of ∼250 × 10 −8 photons cm −2 s −1 , which is typical of its high γ -ray state (Vercellone et al 2008(Vercellone et al , 2009Anderhub et al 2009). As in the case of the previous multifrequency campaign (2007 November; Vercellone et al 2009), the source was continuously monitored in γ -rays as well as in the optical energy bands.…”
Section: Timing Analysismentioning
confidence: 99%
“…AGILE performed a target of opportunity (ToO) re-pointing towards the source and detected it in a very high γ-ray state (Vercellone et al 2008, hereafter V08). In November and December 2007, AGILE detected high γ-ray activity from 3C 454.3, triggering multiwavelength ToO campaigns, whose results are reported in Vercellone et al (2009, hereafter Paper I), in Donnarumma et al (2009, hereafter Paper II), and in Anderhub et al (2009), respectively. Paper I and Paper II demonstrated that to fit the simultaneous broadband SEDs from radio to γ-ray data, inverse Compton (IC) scattering of external photons from the broad line region (BLR) off the relativistic electrons in the jet was required.…”
mentioning
confidence: 60%
“…Rotations of the optical polarisation vector both clockwise and counterclockwise were detected by Sasada et al (2010). In contrast, observations at very high energies (E > 100 GeV) by the Cherenkov telescope MAGIC resulted in only upper limits (Anderhub et al 2009).…”
Section: Introductionmentioning
confidence: 92%